New Insight into Effects of Higher Upper Cutoff Voltage on the Cycling Performance of Graphite‐SiOx/Li‐rich Layered Oxide Pouch‐Type Batteries. Issue 7 (26th May 2022) - Liu, Xingge; Gao, Min; Zhao, Jingling; Sun, Xueyi; Li, Zhao; Wang, Jiantao; Huang, Xiaowei; Zhuang, Weidong
Abstract : High‐energy‐density lithium‐ion batteries based on the graphite–SiO x anode and Li‐rich layered oxide (LLO) cathode are expected to solve the "range anxiety" of electric vehicles, but face undesired capacity degradation. Usually, the rise in upper cutoff voltage (UCV) can increase the capacity but reduce the cycle life. Herein, the effect of different UCVs (4.4, 4.5, 4.6 V) on graphite–SiO x /LLO pouch‐type battery capacity degradation is investigated. Unexpectedly, the batteries at 4.5 and 4.6 V UCVs exhibit the minimum and maximum capacity after 300 cycles, separately. The comprehensive analysis shows that after 300 cycles, a greater loss of anode active material for the battery at 4.5 V UCV occurs, and a larger reversible lithium loss at 4.4 V UCV appears. Nevertheless, for the battery at 4.6 V UCV, a more stable solid electrolyte interphase film generated on the anode slows down the capacity degradation. Abstract : Good and bad: the increase of upper cutoff voltage will have two effects on the cycle performance of the battery. One is to lead more loss of reversible lithium and active materials. The other is to increase more inorganic components in the solid electrolyte interphase film, making it more stable and in turn mitigating the reversible lithium loss and further capacity degradation.